The Impact of Economic Size of Government on Income Distribution: Evidence from OECD Countries - Ceyhan, Turgay; Köstekçi, Ahmet; Göv, Abdullah (Anadolu Üniversitesi, 2021)
In this study, the relationship between taxes and public expenditures, that show the government?s economic size and income distribution, is analyzed. In the study covering the period 2000-2017 for 24 OECD countries, the Two-Step System Generalized Method of Moments and the bootstrap version of Dumitrescu-Hurlin (2012) panel causality test were used. According to the results of the Two-Step System Generalized Method of Moments, the expansion in the government?s economic size increases the inequality. Findings of the panel causality test show unidirectional causality from taxes and expenditures to Gini.